A Review of the Biology of Eucharitidae (Hymenoptera: Chalcidoidea) from Argentina - Torrens, Javier (2013)
All the members of Eucharitidae are parasitoid of ants. Argentina has 14 genera and 41 species, but little is known about their biology. Herein are provided new data for host associations (host ant and/or host plant) of Galearia latreillei, Kapala spp., Latina rugosa, Orasema aenea, and Orasema sp. A revision of the most relevant biological aspects of Dicoelothorax platycerus, Latina rugosa, Neolirata alta, N. daguerrei, Lophyrocera variabilis, Orasema argentina, O. salebrosa, O. simplex, O. susanae, O. worcesteri, and O. xanthopus is included. New records of K. sulcifacies, Lo. plagiata, and Ob. semifumipennis in Argentina are presented. Galearia proseni is synonymized with G. latreillei.